Influence of varying bedding thickness of underclay on floor stability - Jessu, Kashi Vishwanath; Kostecki, T.; Spearing, Sam; Zhang, J. (Elsevier, 2017)
The variation in bedding thickness of the weak immediate floor has long been a challenge in the Illinois basin coal mines when it comes to floor stability. The vertical thickness of the immediate floor is not constant throughout the mines and can vary over short horizontal distances. The biggest misconception from a design standpoint is to use the maximum or average thickness found from core logs taken from various locations on the mine property. The result of this practice is oversized pillars in the areas where the weak immediate floor has thinned vertically. This over-design leaves coal in situ which could have otherwise been extracted. This paper presents a plane strain numerical model to illustrate the effect of a change in bedding thickness of a weak immediate floor across one or two coal pillars. The floor bearing capacity of the variable floor below each pillar where then compared to the consistent floor. The results show that the varying bedding thickness of weak underclay has an impact on the bearing capacity of the floor. Geometrically with the decrease in bedding thickness for constant pillar width, the B/H ratio increases exponentially. The influence of varying bedding thickness on the floor bearing capacity is apparent at higher B/. H ratios. The floor bearing capacity under a single pillar is in variable floor model if the average thickness remains constant. For single pillar, the average of the bedding thickness can be considered and for pillars in a panel, and a safety factor has been proposed to take into account this change in bedding thickness.